Answer:
x=0
Step-by-step explanation:
combine like terms on both sides of the equal sign
-9+x= x-7
move similar terms to the same side
-2=0x
divide both sides by x
x=0
Answer:
Step-by-step explanation:
Flip the equation 1) 8a + 2b = 2x
Subtract 2b from both sides 2)8a + 2b(-2b) =<em> 2x + (-2b)</em>
Divide by 8 on both sides 3) 8a/8 =<em> -2b - 2x/8</em>
4) a = 1/-4b + 1/4x
He should use the Pythagorean Theorem to find the missing length.
Since KT is tangent to the circle and TL reaches the center of circle L, the measure of angle LTK is 90 degrees. This means that triangle LTK is a right triangle which means the Pythagorean Theorem can be used.
So,
TL²+(12)²=(13)²
=> TL²+144=169
=> TL²=25
=> TL = 5
Therefore, the radius of circle L is 5 feet.
The equations of the functions are y = -4(x + 1)^2 + 2, y = 2(x - 2)^2 + 1 and y = -(x - 1)^2 - 2
<h3>How to determine the functions?</h3>
A quadratic function is represented as:
y = a(x - h)^2 + k
<u>Question #6</u>
The vertex of the graph is
(h, k) = (-1, 2)
So, we have:
y = a(x + 1)^2 + 2
The graph pass through the f(0) = -2
So, we have:
-2 = a(0 + 1)^2 + 2
Evaluate the like terms
a = -4
Substitute a = -4 in y = a(x + 1)^2 + 2
y = -4(x + 1)^2 + 2
<u>Question #7</u>
The vertex of the graph is
(h, k) = (2, 1)
So, we have:
y = a(x - 2)^2 + 1
The graph pass through (1, 3)
So, we have:
3 = a(1 - 2)^2 + 1
Evaluate the like terms
a = 2
Substitute a = 2 in y = a(x - 2)^2 + 1
y = 2(x - 2)^2 + 1
<u>Question #8</u>
The vertex of the graph is
(h, k) = (1, -2)
So, we have:
y = a(x - 1)^2 - 2
The graph pass through (0, -3)
So, we have:
-3 = a(0 - 1)^2 - 2
Evaluate the like terms
a = -1
Substitute a = -1 in y = a(x - 1)^2 - 2
y = -(x - 1)^2 - 2
Hence, the equations of the functions are y = -4(x + 1)^2 + 2, y = 2(x - 2)^2 + 1 and y = -(x - 1)^2 - 2
Read more about parabola at:
brainly.com/question/1480401
#SPJ1